2015
DOI: 10.1002/jcp.25054
|View full text |Cite
|
Sign up to set email alerts
|

Cell‐penetrating and endoplasmic reticulum‐locating TAT‐IL‐24‐KDEL fusion protein induces tumor apoptosis

Abstract: Interleukin-24 (IL-24) is a unique IL-10 family cytokine that could selectively induce apoptosis in cancer cells without harming normal cells. Previous research demonstrated that intracellular IL-24 protein induces an endoplasmic reticulum (ER) stress response only in cancer cells, culminating in apoptosis. In this study, we developed a novel recombinant fusion protein to penetrate into cancer cells and locate on ER. It is composed of three distinct functional domains, IL-24, and the targeting domain of transa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…The predominant approach for targeting CPP-bound cargo calls for the fusion of canonical signal sequences to cargo proteins, or even to the CPP tag itself (reviewed in (54)). Using this methodology, cargos have been delivered to the nucleus (55, 56), nucleolus (57), lysosome (58), peroxisome (55), the mitochondria (55, 59, 60) and the endoplasmic reticulum (55, 61), to name a few. Drawbacks to this approach include decreased uptake of tagged CPPs (61) and potential endosomal entrapment en route to the intended compartment.…”
Section: Busting Out: Escape From the Endosomementioning
confidence: 99%
“…The predominant approach for targeting CPP-bound cargo calls for the fusion of canonical signal sequences to cargo proteins, or even to the CPP tag itself (reviewed in (54)). Using this methodology, cargos have been delivered to the nucleus (55, 56), nucleolus (57), lysosome (58), peroxisome (55), the mitochondria (55, 59, 60) and the endoplasmic reticulum (55, 61), to name a few. Drawbacks to this approach include decreased uptake of tagged CPPs (61) and potential endosomal entrapment en route to the intended compartment.…”
Section: Busting Out: Escape From the Endosomementioning
confidence: 99%
“…The levels of BiP/GRP78, phosphorylation of eIF2α, JNK, and c-Jun increased in a concentration-dependent manner (Figure 2D). These results indicated that TAT-IL-24-KDEL induced cancer cell apoptosis via the cell death pathway mediated by ER stress [26]. In addition, the activities of caspase-3 and caspase-7 were increased in a dose-dependent manner (Figure 2E).…”
Section: Resultsmentioning
confidence: 83%
“…In a previous paper, we established an efficient method for obtaining recombinant TAT-IL-24-KDEL in an Escherichia coli expression system containing a SUMO tag [26]. The DNA sequences coding TAT and KDEL were fused with the IL-24 (GenBank No.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations